The impact of family control and CEO duality on earning management: The mediating role of corporate commitment to business ethics - Kartika, Indri; Kartikasari, Lisa (Journal of Advanced Multidisciplinary Research, 2023)
Earnings management is a practice that often occurs in companies, especially in family companies where most stakeholders focus more on profit information. Management always tries to maintain consistent profit figures to gain positive perceptions from stakeholders. Companies controlled by families can take riskier business decisions to maintain the family business socio-emotionally, such as being able to manage and maintain the image well, even though this affects business management. Some studies have examined earnings management in family companies, but only a few have examined the role of corporate commitment to business ethics in creating ethical financial reporting behavior in companies. The sample of this research was 541 manufacturing companies listed on the Indonesian Stock Exchange in 2019-2021 which were analyzed using Multiple Linear Regression Analysis. The research results showed that family ownership and CEO duality have a positive effect on earnings management, but the family members on board have no effect on earnings management. Corporate commitment to business ethics can moderate by strengthening the relationship between family ownership and CEO duality on earnings management, but cannot moderate the relationship between family members on board on earnings management. Investors need to consider aspects of family ownership concentration and CEO duality to see the potential for earnings management.